Consequences of mergers and acquisitions on firm performance: a sector-level study of public listed companies in China / Char-Lee Lok …[et al.] - Lok, Char-Lee; Chen, Yadong; Phua, Lian Kee; Chan, Min Fong (Universiti Teknologi MARA, 2021)
As the motives of mergers and acquisitions (M&As) are different across industries, this study examined the synergy effects of technological gains and capital intensity on the operating performance of the acquiring firms after M&As. The sample comprised 434 completed M&As initiated by Chinese firms listed on the Shanghai and Shenzhen Stock Exchanges with 2,170 observations over the years 2012 to 2016. On average, the firms performed better after M&As. The results show that the operating performance of public health, information technology, telecommunication and financial service firms within the high-technology sector increased after M&As. This suggests that high-technology firms can benefit from M&As through a more extensive knowledge base and financial synergy. We also found that good governance characterized by board independence affects firm performance positively. Therefore, the acquisition of technology through M&As could be an essential corporate growth strategy in the Chinese capital market, which is transforming from a state-controlled economy to a more market driven one. The findings provide useful insights to both corporate players and policy-makers on the types of M&As that stand higher chances to generate positive outcomes and those that need extra measures and further scrutiny to prevent inefficient allocation of resources.